Colloidal nanoparticle inks for printing active layers in optoelectronic devices

Through the two-phase ligand exchange process, the non-polar ligand of the colloidal quantum dots is replaced with polar ligand, which solves the problems of ink incompatibility and poor electron properties, and realizes the stability of nanoparticles and the optimized properties of ink .

CN115349005BActive Publication Date: 2025-02-21UNIVERSITY OF GRONINGEN +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180016032.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-25
Filing Date
2021-02-24
Publication Date
2025-02-21
Estimated Expiration
2041-02-24

AI Technical Summary

Technical Problem

Prior Art When manufacturing inks suitable for electronic devices, there are problems such as colloidal quantum dot solution incompatibility, poor membrane electron properties, and nanocrystal degradation or aggregation during ligand exchange.

Method used

By using a two-phase ligand exchange process, the first ligand bound to the nanoparticles is replaced by mixing the polar solvent with the second ligand, thereby forming a dispersion of nanoparticles encapsulated by the second ligand shell and replacing it again Dispersed in a printable liquid medium.

Benefits of technology

The properties of ink are optimized, the risk of degradation of nanoparticles is reduced, the optical and electronic properties of nanoparticles are maintained, and high-quality inks suitable for optoelectronic devices are provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115349005B_ABST
    Figure CN115349005B_ABST
Patent Text Reader

Abstract

A method for making an ink (100) composition comprises a two-phase ligand exchange process. A first phase liquid (10) comprising a non-polar solvent (11) and a colloidal suspension of nanoparticles (1) terminated by shells of non-polar ligands (2) is contacted with a second phase liquid (20) comprising a polar solvent (21) and a second ligand (3). The second ligand comprises at least one surface-binding head group having an affinity for binding to the nanoparticles; and an ionically charged tail group. The second ligand displaces the first ligand to form a dispersion of nanoparticles terminated by shells of the second ligand in the second phase liquid. The nanoparticles can be separated from the second phase liquid. The separated nanoparticles can be (re)dispersed in a printable liquid medium, for example for printing a photoactive layer.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Technical Field and Background

[0002] The present disclosure relates to (making) inks having colloidal nanoparticles (eg, quantum dots), particularly inks and compositions suitable for depositing (eg, printing) active layers (eg, active layers for optoelectronic devices).

[0003] Colloidal suspensions of nanoparticles, nanocrystals and / or quantum dots have a wide range of applications, including for the manufacture of electronic devices such as field effect transistors (FETs), solar cells, light emitting FETs, light emitting diodes, photodetectors for visible light, IR, X-rays or gamma radiation, phototransistors, thermoelectric elements, bolometers, etc. Similarly, water-based dispersions of quantum dots can be used as platforms for biological applications. Linkers, such as ligands on the surface of quantum dots, allow, for example, the manufacture of conjugates of various biomolecules using quantum dots as fluorescent markers.

[0004] Colloidal quantum dots typically include nanocrystals of inorganic materials with discrete energy levels due to quantum confinement of electrons within the volume of the nanoparticles. Quantum dots can be synthesized in the form of colloidal solutions of quantum dots and can be dispersed in non-polar organic solvents such as hexane after purification. In the colloidal solution, each quantum dot is terminated with a long aliphatic molecule called a ligand. For example, these ligands can include oleic acid (OA) or oleylamine (OAm), which bind to the surface of the quantum dot through a carboxyl or amine group. The aliphatic tail of the ligand ensures the colloidal stability of this quantum dot solution, generating a repulsive force between the quantum dots, offsetting the attractive component of the van der Waals force acting on a particle close to another particle. This stabilization mode is called spatial stabilization of the colloid. However, this quantum dot solution is generally not suitable for direct application. For example, non-polar solvents may be incompatible with the intended biological application. In addition, films deposited from this quantum dot solution generally show very poor electronic properties. One method to overcome this problem includes the use of phase transfer ligand exchange, which is a method of replacing the ligand on the surface of the quantum dot with a different entity (e.g., ligand). Typically, the process is carried out in solution.

[0005] As background technology, US6251303B1 discloses a method for making water-soluble fluorescent nanocrystals. In this method, fluorescent nanocrystals with non-polar ligand ends are separated from a suspension. The non-polar ligands are exchanged for different precursor ligands by exposing the separated fluorescent nanocrystals to a new solution containing 30 times excess of the precursor ligand at an elevated temperature. The nanocrystals can be made water-soluble in a separate step by protonating the precursor ligand. In addition to a large number of delicate manufacturing processes, the disadvantages of the disclosed method also include: the presence of non-polar ligands and / or the presence of a large amount of excess unbound precursor ligands in the formed composition; and / or possible nanocrystal degradation or agglomeration due to the length of time it is exposed to the elevated temperature.

[0006] As further background, Hak Soo Choi et al. (Nature Biotechnology 25; 1165-1170 (2007)) disclose a ligand exchange process that can provide CdSe / ZnS core-shell quantum dots terminated by cysteamine for biological applications. The process uses a water / chloroform-based ligand exchange process, wherein the aqueous phase is provided with a phosphate-buffered saline buffer to dissolve the quantum dots. As a result, the quantum dot suspension formed contains a large amount of salt and / or a large excess of unbound ligands, making them less suitable for manufacturing electronic devices.

[0007] As other background technology, Byung-Ryool Hyun et al. (J.Phys.Chem.B 2007,111,20,5726-5730) discloses a multi-step method for making water-soluble lead salt quantum dots for near-infrared fluorescence imaging. The method uses a large excess of ligands and includes precipitation of QDs, followed by a reaction that makes the quantum dots water-soluble.

[0008] As other background technology, Noipa T et al. (Spectrochim Acta A Mol Biomol Spectrosc. 2014 Jan 24; 118: 17-23) disclosed the preparation of Fe 3+ Methods for modified cysteamine CdS quantum dots as fluorescent sensors for the detection of pyrophosphate. CdS quantum dots were synthesized directly with cysteamine ligands using a one-pot synthesis method. During the synthesis, the dots did not benefit from the stabilizing effect of the long aliphatic ligands. The dots formed were found to be of lower quality and therefore less suitable for use in electronic grade quantum dot inks.

[0009] As further background, US2007174939A1 discloses a method for preparing quantum dot films for optical and optoelectronic devices. The method includes prefabricated quantum dots and ligand exchange. Similar to US6251303B1, ligand exchange includes precipitating the as-synthesized quantum dots from their original solution and dispersing the separated particles in a liquid containing exchange ligands. Therefore, the method of US2007174939A1 has one or more disadvantages described with respect to US6251303B1. Summary of the invention

[0010] The method for making an ink composition comprising a two-phase ligand exchange process according to the present invention is intended to alleviate one or more of the above-mentioned disadvantages and / or provide one or more other advantages when making electronic devices from the ink composition.

[0011] Aspects of the present disclosure relate to methods for making ink compositions. A first phase liquid comprises a non-polar solvent and a suspension of nanoparticles dispersed in the non-polar solvent (colloidal suspension). The nanoparticles, such as quantum dots, can be capped by a shell of a first ligand comprising a surface-binding head group and an alkyl or alkenyl tail, for at least initially maintaining the nanoparticles (quantum dots) in a colloidal suspension in the non-polar solvent. A second phase liquid comprises a polar solvent and a second ligand dissolved therein. The second ligand has a molecular structure that preferably includes at least one surface-binding head group, and the surface-binding head group has an affinity for binding to the surface sites of the nanoparticles. In addition, the structure preferably includes at least an ionically charged tail group and a counterion associated therewith. A two-phase ligand exchange process can be used, in which the second ligand displaces the first ligand bound to the nanoparticle. This can result in the release of the first ligand to the first phase liquid. Typically, the two-phase ligand exchange process includes contacting the first phase liquid and the second phase liquid. This can form a dispersion of nanoparticles (e.g., quantum dots) capped by the shell of the second ligand in the second phase liquid. The nanoparticles terminated by the shell of the second ligand can be separated from the second phase liquid. The separated nanoparticles terminated by the shell of the second ligand (quantum dots) can be (re)dispersed in a printable liquid medium. In this way, an ink can be formed, the printing properties of which can be further adjusted, for example by adding other or additional additives.

[0012] Other aspects of the present disclosure relate to dried compositions comprising nanoparticles, preferably quantum dots, capped with a shell of a second ligand obtainable by any of the methods described herein, wherein the method further comprises drying the isolated quantum dots capped with a shell of a second ligand.

[0013] However, other aspects of the present disclosure relate to ink compositions comprising nanoparticles terminated by a shell of a polar organic ligand. The ink composition comprises a colloidal suspension of quantum dots in a polar printable liquid medium, wherein the quantum dots are terminated by a shell of a second ligand, and wherein the second ligand has a molecular structure comprising: at least one surface-binding head group having an affinity for binding to a surface site of the quantum dot; and an ionically charged tail group and a counter ion associated therewith.

[0014] Further aspects relate to the use of a dried composition obtainable according to the disclosed method in the manufacture of a printable ink composition, and the use of an ink as described herein (preferably a quantum dot-based ink) for the manufacture of an optoelectronic device. Accordingly, aspects of the present disclosure also relate to a method for manufacturing an imaging device, the imaging device comprising a stack of photoactive layers, the stack of photoactive layers comprising at least a p-type photoactive layer and / or an n-type photoactive layer. The method comprises: depositing one or more layers of an ink composition comprising a p-type dopant as described herein or an ink obtainable by a method as described herein; and depositing one or more layers of an ink composition comprising an n-type dopant as described herein or an ink obtainable by a method as described herein to form a stack of photoactive layers comprising at least a p-type photoactive layer and / or an n-type photoactive layer, and wherein the photoactive layer is amorphous and comprises a disordered structure of nanoparticles resulting from the deposition of the corresponding ink composition.

[0015] As will be explained below, the disclosed methods, inks and intermediate products provide certain advantages. These advantages include providing an easy and / or universal ligand exchange process that allows the manufacture of quantum dots terminated by a variety of second ligands. Advantageously, since the manufacture of the ink can be carried out at room temperature and / or in the absence of harsh conditions (e.g., not exposed to high concentrations of strong acids or bases), nanoparticle degradation can be mitigated. In addition, the nanoparticles terminated by the shell of the second ligand are separated from the second phase containing the first polar solvent, and the quantum dots are redispersed in a liquid of different polarity (e.g., a liquid printing medium), which allows the properties of the ink to be optimized, such as the type of solvent contained therein, regardless of the selection criteria for the ligand exchange process control.

[0016] In addition, the optical and electronic properties of the obtained nanoparticles can remain stable, for example, over an extended period of time, because the obtained dried composition of nanoparticles terminated by a shell of a second ligand can be stored without losing the necessary functionality. Advantageously, the stored composition can be (re)dispersed in a suitable printable liquid medium before use.

[0017] The two-phase ligand exchange process according to the present invention can be understood as producing capped nanoparticles, which are found to be particularly beneficial for use in the manufacture of photoactive layers of optoelectronic devices by providing a combination of favorable properties. Advantages include the discovery that the particles manufactured according to the disclosed method are substantially free of hydrophobic ligand moieties and / or oily or waxy impurities associated with the synthesized nanoparticles. As such, the two-phase ligand process according to the present invention can be understood as a purification or cleaning procedure that allows the initial hydrophobic capping layer to be substantially replaced by a replacement capping layer of different functional moieties as disclosed herein, including possible contaminants. As will be explained herein, the replacement capping layer provides improved optoelectronic properties. In addition, it was found that the replacement capping layer effectively stabilizes the nanoparticles in a dried form while allowing the dried particles to be (re)dissolved in an ink composition comprising a polar solvent, which is used to manufacture the photoactive layer of an optoelectronic device. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] These and other features, aspects, and advantages of the apparatus, systems, and methods of the present disclosure will become better understood from the following description and examples, the appended claims, and the accompanying drawings, in which:

[0020] Figure 1A A two-phase ligand device is schematically shown;

[0021] Figure 1B Schematically illustrates a two-phase ligand exchange process at an initial stage, e.g., shortly after bringing the liquids into contact;

[0022] Figure 2A A later stage of the two-phase ligand exchange process is schematically shown;

[0023] Figure 2B schematically illustrates a container containing isolated nanoparticles capped with a shell of a second ligand;

[0024] FIG. 3A to FIG. 3F Schematically depicting various second ligands for use in the methods described herein;

[0025] Figure 3G schematically depicts exemplary polymer additives for use in inks as described herein;

[0026] Figure 4A The steps in making the ink composition are schematically depicted;

[0027] Figure 4B schematically depicts a container having an ink composition;

[0028] Figure 5 schematically illustrates a cross-sectional side view of an imaging device including a photoactive layer made using an ink as described herein;

[0029] Fig. 6A schematically illustrates the color changes observed during an embodiment of the method as described herein;

[0030] FIG. 6B to FIG. 6D showing photographs of vials at various stages during embodiments of the methods as described herein;

[0031] FIG. 7A to FIG. 7B The optical properties of exemplary quantum dot compositions are shown;

[0032] FIG. 8A to FIG. 8B The optical properties of exemplary quantum dot compositions are shown;

[0033] Figure 8C Aspects of large-scale manufacturing are shown;

[0034] FIG. 9A to FIG. 9B The properties of exemplary optoelectronic devices incorporating quantum dots are shown;

[0035] FIG. 10A to FIG. 10B The properties of exemplary optoelectronic devices incorporating quantum dots are shown;

[0036] FIG. 11A to FIG. 11B The properties of exemplary optoelectronic devices incorporating quantum dots are shown;

[0037] FIG. 12A to FIG. 12B The properties of exemplary optoelectronic devices incorporating quantum dots are shown;

[0038] FIG. 13A to FIG. 13B properties of exemplary optoelectronic devices incorporating quantum dots are shown; and

[0039] FIG. 14A to FIG. 14B Properties of exemplary optoelectronic devices incorporating quantum dots are shown. DETAILED DESCRIPTION

[0040] The terms used to describe specific embodiments are not intended to limit the present invention. As used herein, the singular forms "a", "an", and "the" are also intended to include plural forms, unless the context clearly indicates otherwise. The term "and / or" includes any combination and all combinations of one or more of the relevant listed items. It should be understood that the terms "include" and / or "comprise" specify the presence of the features, but do not exclude the presence or addition of one or more other features. It should also be understood that when a particular step of a method is referred to as being after another step, it can be directly placed after the other step, or one or more intermediate steps can be performed before performing the particular step, unless otherwise stated. It should also be understood that when describing a connection between a structure or component, the connection can be established directly, or the connection can be established through an intermediate structure or component, unless otherwise stated.

[0041] Unless otherwise stated, properties of compounds of mixtures referred to herein, such as solubility, are specified at room temperature and standard pressure, eg, 20 degrees Celsius and one atmosphere.

[0042] (Colloidal) nanoparticles comprise a dense core of an inorganic material having at least one dimension less than 1000 nanometers, such as 1 or 10 angstroms to 100 nm, preferably about 1 nanometer to about 50 nanometers, such as about 2 nanometers to 10 nanometers, such as 3 nanometers. Colloidal nanocrystals (NCs) of semiconductor materials having unique electronic properties determined by their size are often referred to as quantum dots (QDs) or colloidal quantum dots (QCDs) due to quantum confinement effects. The advantages of QDs include: size-tunable band gaps, high light absorption coefficients, and solution processability.

[0043] Quantum dots synthesized by solution are generally referred to as colloidal quantum dots or colloidal nanocrystals. After synthesis, colloidal quantum dots are usually capped by long aliphatic ligands (e.g., oleic acid or oleylamine) to ensure uniform growth of nanoparticles and colloidal stability of solution. For some nanoparticles, other ligands can be used, including but not limited to various phosphines and phosphine oxides (e.g., trioctylphosphine and trioctylphosphine oxide). Quantum dots can be manufactured using other methods including plasma synthesis. Quantum dots synthesized by plasma are usually in powder form, to which surface modification can be performed, such as passivation with aliphatic ligands.

[0044] Nanoparticles have been reported for a wide range of compositions. Examples include single element nanoparticles (Ag, Au, Ni, Ru, Rh, Pd, Pt, Sn, Si, Ge, Ga, In, Fe, Mn, Co, Cu, Be, C, B, Al, Sb, Li, Na, K, Y, lanthanides, etc.), carbonaceous-based nanoparticles, metal and / or lanthanide oxide nanoparticles (Fe 2 O 3 , Fe 3 O 4 、MnO、Mn 2 O 3 , Mn 3 O 4 , MgO, CaO, BaO, ZnO, TiO 2 、NiO、Ni 2 O 3 、In 2 O 3 , Ga 2 O 3 、Be 2 O 3 , Y 2 O 3 、SiO 2 、V 2 O 3 、V2 O 5 、CeO 2 、Al 2 O 3 ,GeO 2 、ZrO 2 , HfO 2 , CuO, Cu 2 O、SnO 2 , WO 3 、Au 2 O 3 ,BaFe 12 O 19 、As 2 O 3 、Bi 2 O 3 、Bi 2 O 5 、CoO、CdO、PbO、HgO、Au 2 O 3 , Li 2 O、Na 2 O.K 2 O、Rb 2 O、Cs 2 O, SrO, Ln 2 O 3 (wherein Ln represents a lanthanide element, etc.), chalcogenide nanoparticles (e.g., ZnX, CdX, PbX, HgX, BiX, Cu 2 X, CuX, Bi 2 X 3 、Bi 2 X 5 、In 2 X 3 、Al 2 X 3 , GaX, Ga 2 X 3 、SnX、SnX 2 、FeX、FeX 2 、NiX、Ni 2 X 3 , CoX, Co 2 X 3 、GeX 2 、MnX、Mn 2 X 3 、Ag 2 X, MoX 2 , WX 2 Cr 2 X 3 (where X represents S, Se or Te)), nitride nanoparticles (BX, AlX, GaX, InX, Si3 X 4 (where X represents N, P, As or Sb)), carbide nanoparticles (SiC, TiC, WC, MoC 2 , HfC, ZrC) and mixtures thereof. It should be understood that particles suitable for use in the present invention should not be construed as limited to the exemplary compositions listed. Particles comprising mixtures or combinations of the above materials may also be used advantageously, including, for example, core / shell structures or segmented particles, and alloys (e.g., AgInS 2 ) and / or doped particles.

[0045] The shape of the nanoparticles can be understood to include, but are not limited to, spheres, cylinders, disks, toroids, wires, rods, needles, cubes, cuboctahedrons, parallelepipeds (blocks), tetrahedrons, octahedrons, icosahedrons, dodecahedrons, prisms, nanoplates of various shapes (square, triangle, rectangle, hexagon, etc.), nanofoils, nanotubes, stars, tetrapods, hyperbranched and branched. The above nanoparticles can be provided in a core / shell configuration or a core / shell / shell structure with layers of different compositions, wherein the interface between the layers of different compositions can be a sudden change interface or a gradual change interface. The nanoparticles can be hollow or porous, or one or more materials of two or more shapes can be combined.

[0046] Should be understood that the two-phase ligand exchange process as described herein can be advantageously used for a variety of nanoparticles, including nanocrystals and quantum dots. The method or steps described below in conjunction with the explanation of a particular type of nanoparticle (e.g., quantum dots) should not be inferred to be limited to the nanoparticles of this particular type. On the contrary, it can be understood that the selection of nanoparticle types depends on the target application, such as based on the requirements of the active components in the optoelectronic device.

[0047] Unless otherwise specified, it is understood that non-polar solvents as used herein include linear-, branched-, cyclic- or halogenated alkanes, alkenes and alkynes, as well as aromatic compounds. Non-polar solvents include, but are not limited to, pentanes (such as n-pentane and 2,2,4-trimethylpentane), hexanes (such as n-hexane), heptanes, octanes, nonanes, decanes, dodecanes, hexadecanes, 1-octadecene, petroleum ether, poly(α-olefins) and oligo(α-olefins), squalane, cyclopentane, cyclohexane, benzene, toluene, ethylbenzene, xylenes (such as p-xylene), trimethylbenzene, cumene, chlorobenzene, dichlorobenzene, 1,2,4-trichlorobenzene, fluorobenzene, difluorobenzene, hexafluorobenzene, biphenyl, diphenyl ether, cresol, terphenyl, mesitylene, nitrobenzene, tetralin, decalin, dichloromethane, chloroform, tetrachloromethane, carbon disulfide, trichloroethylene, 1,1,1-trichloroethane, tetrachloroethylene, ethyl acetate, diisopropyl ether, diethyl ether, and mixtures thereof.

[0048] Unless otherwise specified, it is understood that the polar solvents used herein include, but are not limited to, methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, glycerol, 1,3-butanediol, ammonia, hydrazine, acetone, acetonitrile, benzonitrile, formamide, N-methylformamide, dimethylformamide, dimethylacetamide, dimethyl sulfoxide, hexamethylphosphoramide, propylene carbonate, N-methyl-2-pyrrolidone, nitromethane, methylamine, dimethylamine, ethylamine, propylamine, butylamine, triethylamine, trimethylamine, ethanolamine, methoxyethanol, ethylenediamine, dimethylethylenediamine, tetramethylethylenediamine, tetrakis(dimethylamino)ethylene, pyridine, 2,6-difluoropyridine, water, and mixtures thereof.

[0049] The present invention will be described more fully below with reference to the accompanying drawings, in which embodiments of the present invention are shown. In the accompanying drawings, the absolute and relative sizes of systems, components, layers and regions may be exaggerated for clarity. The embodiments may be described with reference to schematic and / or cross-sectional illustrations of possible idealized embodiments and intermediate structures of the present invention. In the specification and drawings, the same numbers refer to the same elements throughout. Relative terms and their derivatives should be interpreted as referring to orientations as described subsequently or as shown in the drawings discussed. These relative terms are for ease of description and do not require that the system be constructed or operated in a specific orientation unless otherwise stated.

[0050] 1-2 schematically illustrate the manufacture of an ink composition 100 at different stages.

[0051] Figure 1A A two-phase ligand device is schematically shown. The device shown is formed by a container 50, such as a beaker. Of course, other devices can also be used. Preferably, the container has at least one transparent side wall portion, so that the progress can be followed visually.

[0052] A first phase liquid 10 is added to a container 50. The first phase liquid 10 comprises a non-polar solvent 11 or a mixture of non-polar solvents, or is substantially formed by a non-polar solvent 11 or a mixture of non-polar solvents. A suspension (colloidal suspension) of quantum dots 1 is dispersed in the solvent. The quantum dots 1 are capped with a shell 2s of a first ligand 2. The ligand comprises a surface-binding head group 2h that binds to a surface site on the quantum dot. The ligand also comprises a non-polar alkyl or alkenyl tail group 2t, which is used to at least initially maintain the quantum dots 1 in a colloidal suspension in the non-polar solvent 11. The shell 2s of the first ligand (represented by a dotted circle) is sometimes referred to as a crown, which can be understood to include a volume around the quantum dot occupied by the second ligand. Quantum dots synthesized from a solution are generally referred to as colloidal quantum dots or colloidal nanocrystals. After synthesis, colloidal quantum dots are generally capped with long aliphatic ligands (such as oleic acid or oleylamine), which is believed to ensure uniform growth of nanoparticles and colloidal stability of the solution. Quantum dots can be made using other methods including plasma synthesis. For quantum dots that do not yet comprise a shell of a first ligand, such as quantum dot powder synthesized by plasma, the method comprises a step of capping the quantum dots with a shell 2s of a first ligand 2 .

[0053] Typically, the type and / or composition of quantum dots can depend on their desired application. The methods disclosed herein should not be construed as being limited to a certain type and / or composition of quantum dots themselves. It was found that the disclosed methods of forming inks are applicable to a wide range of quantum dots that are terminated with a shell of an aliphatic ligand that is sufficiently unstable to be replaced by a second ligand. Suitable quantum dots include, but are not limited to, Au, PbS, PbSe, and CdSe quantum dots, as well as multilayer dots comprising such an outer coating.

[0054] The second phase liquid 20 is added to the container 50. The second phase liquid comprises or is substantially formed of a polar solvent 21 or a mixture of polar solvents in which a certain amount of the second ligand 3 is dissolved.

[0055] Optionally, a third solvent (co-solvent) can be added to the two-phase mixture. The third solvent is miscible with the liquids constituting the first phase liquid and the second phase liquid. It has been found that adding a co-solvent promotes and accelerates ligand exchange. The miscibility of the third solvent is defined as forming a single-phase fluid with an equal volume of non-polar solvent and an equal volume of the first polar solvent, respectively.

[0056] The second ligand has a multi-block molecular structure, which includes at least one surface-binding head group 3h, which has an affinity for binding to the surface site of the quantum dot 1; and an ionic tail group 3t and a counter ion 3c associated therewith. Typically, the second ligand comprises an organic spacer 3s that separates the head group and the tail group. Details about the second ligand will be described later. It was found that no other additives such as pH buffers were required to drive the ligand exchange reaction to completion. As additives, such as pH buffers or ionic strength modifiers, may be particularly difficult to remove, and / or may negatively affect the optoelectronic properties of quantum dots, the second phase liquid preferably does not contain such additives, i.e., is composed of a solution of one or more second ligands in a polar solvent or a mixture of solvents.

[0057] It can be understood that the first phase liquid and the second phase liquid are substantially immiscible. Substantially immiscible liquids, such as the first phase liquid and the second phase liquid, can spontaneously form a two-phase liquid system. Providing substantially immiscible phases can advantageously be relatively easily separated from each other, such as by decantation or pouring. The exact composition of the first phase liquid and the second phase liquid can depend on the type of quantum dots and / or the type of the first ligand that caps the quantum dots. Preferably, the first phase liquid can disperse the quantum dots capped with the shell of the first ligand at a concentration of at least 10 mg / ml. Similarly, the first phase liquid can preferably dissolve the first ligand at a concentration of at least 10 mM.

[0058] The second phase liquid is a poor dispersion medium for the first ligand and the quantum dots terminated by the shell of the first ligand. Preferably, the solubility of the first ligand in the second phase liquid is less than 0.1 mM. Preferably, the solubility of the quantum dots terminated by the first ligand in the second phase liquid is less than 0.1 mg / ml, or lower, such as less than 0.01 mg / ml, preferably negligible. The second phase liquid is a good solvent for the second ligand. The higher the solubility of the second ligand, the better dispersion medium the second phase liquid can be for the quantum dots terminated by the shell of the second ligand. The solubility of the second ligand is preferably at least 10 mM, preferably higher such as at least 20 mM, or higher such as at least 30 mM. The higher the concentration of the second ligand, the faster the ligand exchange reaction can be.

[0059] The first phase liquid and the second phase liquid can each independently comprise a single solvent or a mixture of solvents. In some embodiments, the first phase liquid comprises a non-polar solvent or a mixture of non-polar solvents. It can be understood that non-polar solvents, which are sometimes referred to as non-polar solvents, include solvents with low net dipole moments. Preferably, the non-polar solvent has a dipole moment (Debye unit / 1x10) less than 1.5D. -18Electrostatic Coulomb-cm). The lower the dipole moment of the solvent, the lower the solubility of the polar compound in the solvent. More preferably, the dipole moment of the non-polar solvent is less than 1.0D or lower, for example, less than 0.5D, for example 0.35D to 0D. The choice of the first phase liquid comprising one or more polar solvents may be limited by the availability of quantum dots terminated by the shell of the first ligand, for example commercial availability. For quantum dots terminated by the shell of a ligand comprising a surface binding head group and an alkyl or alkenyl group having a carbon number n of 12 to 20 (e.g., oleic acid, oleylamine, octadecylamine, and hexanoic acid), the inventors found that a suitable first phase liquid comprises one or more aliphatic solvents, or is substantially composed of one or more aliphatic solvents, the aliphatic solvents including but not limited to hexane and octane. It can be understood that the polar solvent 21 includes a solvent with a high net dipole moment. Preferably, the polar solvent has a dipole moment higher than 1.5D (Debye unit / 1x10 -18 Electrostatic Coulomb-cm). The higher the dipole moment of the solvent, the lower the solubility of the non-polar compound in the solvent. More preferably, the dipole moment of the polar solvent is higher than 1.6D or higher, such as higher than 2, such as 1.5 to 5.

[0060] It is found that the difference in dipole moment and / or logP (n-octanol / water) provides further selection criteria. It is found that the difference in dipole moment between the first phase liquid and the second phase liquid is preferably at least 0.5D. The higher the difference, the lower the mutual solubility between the liquid phases. Preferably, the difference in dipole moment between the first phase liquid and the second phase liquid is higher, for example at least 0.7D or at least 1.0D or greater. It is generally found that suitable polar solvents have negative logP values. It is generally found that solvents with negative logP values ​​are good solvents for the second ligand. Preferably, the logP of the polar solvent is lower than about -0.2. It is generally found that solvents with lower logP values ​​are less miscible in the first phase liquid and / or are not very good solvents for the first ligand.

[0061] By adding a first phase liquid and a second phase liquid including their respective components into a common container, a two-phase system is formed, wherein the respective liquids separate at a common interface. A cross-interface ligand exchange process, a two-phase ligand exchange process, can be initiated, wherein the second ligand replaces the first ligand bound to the quantum dot 1.

[0062] Figure 1BThe two-phase ligand exchange process is schematically shown in the initial stage, such as shortly after the liquids are contacted. Contact generally includes adding the first phase liquid and the second phase liquid to a common container 50 (e.g., a vial). The second phase liquid can be added to a container provided with a certain amount of the first phase liquid, or vice versa, that is, the first liquid is added to a container containing the second phase liquid. Optionally or additionally, the second ligand or a portion thereof can be added in a separate step, such as added to a common container containing the first phase liquid and the second phase liquid, such as in response to the observed or determined progress of the ligand exchange reaction. In the figure shown, the first phase liquid 10 containing the non-polar solvent 11 and the quantum dots 1 terminated by the shell of the first ligand 2 and the second phase liquid 20 containing the polar solvent 21 and the second ligand 3 interact at the common interface 19 (represented by dot-dash lines in the figure). As the reaction is carried out across the interface, the increased contact area can reduce the required contact time. In order to increase the effective area of ​​contact, the method preferably includes stirring the first phase liquid and the second phase liquid in contact, such as by shaking or stirring.

[0063] At the interface, the ligand (first ligand 2) initially bound to the surface of the quantum dot 1 is replaced by the second ligand 3. It is believed that the exchange reaction proceeds because the head group 3h of the second ligand 3 has a higher affinity for the surface of the quantum dot than the affinity of the head group 2h of the first ligand 2. The replaced first ligand portion is thus referred to as a ligand released into the first phase liquid 10.

[0064] Figure 2A A later stage of the two-phase ligand exchange process, i.e., during contacting of the first phase liquid 10 and the second phase liquid 20, is schematically shown. By contacting the first phase liquid 10 and the second phase liquid 20 for a suitable time, the exchange reaction can proceed to completion, forming a dispersion of quantum dots 1 capped by the shell 3s of the second ligand 3 in the second phase liquid. As the reaction proceeds, the second ligand 3 in the solution is partially consumed and incorporated in the shell 3s. In some embodiments, for example, as shown, after substantially all of the quantum dots 1 are capped by the shell 3s of the second ligand 3, the second phase liquid 20 may contain a remaining portion (excess) of the ligand 3'.

[0065] In some embodiments, the method includes washing the second phase liquid 20 containing quantum dots capped by the shell 3s of the second ligand with one or more portions of a solvent for the first ligand. Washing the quantum dots capped by the shell 3s of the second ligand in the second phase liquid 20 with one or more portions of a solvent for the first ligand can reduce the amount of free (unbound) first ligands in the product, which can be dissolved in the liquid 20 at a lower concentration. Contaminants, such as excess ligands, can form non-conductive or interfering domains in the printed layer of quantum dots. Therefore, excess ligands can adversely impart properties, such as conductivity, to the sensing material layer.

[0066] In some embodiments, a dispersion of quantum dots 1 capped by shells 3s of second ligands in a second phase liquid may be considered an ink composition 100. As will become clear below, quantum dots 1 capped by shells 3s of second ligands 3 are preferably separated from the second phase liquid.

[0067] The quantum dots 1 terminated by the shell 3s of the second ligand 3 are preferably substantially free of contaminants, i.e., of high purity. It has been found that contaminants, such as unbound ligands, salts, greases and / or waxes, adversely affect the optoelectronic properties of the particles, such as the optoelectronic properties of a film formed by an ink comprising the particles and impurities. Reducing the introduction of impurities and / or reducing the level of impurities is preferred over subsequent removal or purification procedures, since such subsequent cleaning or purification procedures (e.g., washing steps) may affect particle stability. It will be understood that purity is defined as the mass fraction of quantum dots having a shell of the second ligand in the final dry powder. Preferably, the purity of the quantum dots is 90%, more preferably greater than 99%.

[0068] Figure 2B A container 51 containing separated quantum dots 1 capped by the shell 3s of the second ligand is schematically shown. The separated quantum dots 1 capped by the shell 3s of the second ligand can be obtained by separating the quantum dots capped by the shell of the second ligand from the second phase liquid. Separation of the quantum dots capped by the shell of the second ligand from the second phase liquid (including the possible excess of unbound second ligand dissolved therein) is preferably carried out by separating the second phase liquid from the first phase liquid, for example, by decantation, pouring or suction.

[0069] The separation of the quantum dots terminated by the shell of the second ligand from the second phase liquid can be achieved by any suitable method known in the art. Preferably, the separation can be achieved by centrifugation to precipitate the quantum dots terminated by the second ligand from the polar phase. Centrifugation is found to be a reliable and rapid method for separating particles from a suspension to form a pellet of quantum dots 1 terminated by the shell 3s of the second ligand 3. The separated quantum dots, for example in the form of pellets, can be easily removed and stored. When provided in a dry form, for example, substantially in a solid form, it is found that the quantum dots terminated by the shell of the polar ligand show improved stability compared to quantum dots stored in a fluid. Storage in a dry form can reduce quantum dot degradation, for example due to Oswald ripening. In an inert atmosphere (e.g., N 2 ) can further mitigate quantum dot degradation (e.g., due to oxidation). In some embodiments, separation includes adding an antisolvent to precipitate the quantum dots. The supernatant containing a possible excess of free unbound second ligands can be discarded. Preferably, separation also includes a drying step, such as a vacuum drying step, to evaporate the remaining solvent.

[0070] The second ligand comprises at least one surface-binding head group having an affinity for binding to a surface site of the quantum dot; and an ionic tail group and a counterion associated therewith. The head group of the second ligand is bound to the surface of the quantum dot via a heteroatom, i.e., the surface atom of the quantum dot. The properties of the quantum dot, i.e., the type of binding sites available on the outer surface of the quantum dot, can determine the selection of the type of surface-binding head group of the second ligand. The surface-binding head group comprises one or more heteroatoms selected from O, S, Se, Te, N, P, and As. It is known that moieties containing sulfur-based functional groups, such as thiols, thioesters, and disulfides, are easily bound to a variety of surfaces by forming covalent metal-sulfur bonds. Suitable surfaces include metal surfaces such as Au and Ag, and semiconductor surfaces, including but not limited to chalcogenide materials such as CdS, CdSe, PbS, and PbSe. Therefore, for quantum dots whose outer surfaces contain such materials, the surface-binding head of the second ligand is preferably based on sulfur groups.

[0071] The charged tail group of the second ligand provides a shell including a charged group for quantum dots. The charge functional group can be provided by a permanent ionic charge or a charged functional group, such as a conjugate acid of a weak base or a conjugate base of a weak acid. Suitable charged tail groups include but are not limited to carboxylate, sulfonic acid, phosphite, phosphonate, hydroxyl, sulfonate, amine, quaternary ammonium salt, carbocation, carbanion, etc. In some embodiments, the charged tail group includes an acid adduct of a weak organic base, such as a hydrochloride adduct of a primary amine, a secondary amine or a tertiary amine. In other or additional embodiments, the charged tail group includes a water-soluble salt of an organic acid, such as sodium carboxylate or sodium sulfonate.

[0072] The organic spacer separating the head group and the tail group can in principle be formed by any organic group that connects and covalently connects the head group and the tail group. Depending on the desired application of the quantum dots, the nature of the linking group can play a more or less important role. For example, in applications where the quantum dots are contained in a dense functional layer (such as a conductive sensing layer), the size or length of the spacer affects the spacing between adjacent quantum dots within the dense layer of quantum dots. Preferably, the organic spacer is a short spacer. The shorter the spacer, the closer the quantum dots are, that is, the smaller the interparticle spacing in the sensing layer formed by the ink containing quantum dots terminated by the second ligand. The shorter the interparticle spacing, the better the optoelectronic properties. Preferably, the spacer is an aliphatic spacer, such as -C n H 2n -, wherein the number of carbon atoms (n) is equal to 1, 2 or 3.

[0073] Figure 3A A Markush formula representing a class of second ligands 3 as described herein is schematically depicted. Figure 3AThe class of compounds depicted in contains a thiol head group (SH) for binding the second ligand to the surface of the quantum dot. The charged tail group (Y) represents: an acid adduct of a weak organic base, such as a hydrochloride adduct of a primary, secondary or tertiary amine; or a water-soluble salt of an organic acid, such as a sodium carboxylate or sodium sulfonate. The spacer is an alkyl spacer having a total number of carbon atoms n of 1 to 3. In some preferred embodiments, the charged tail group is formed by an acid adduct of an organic amine, such as Figure 3C As shown in 1 and R 2 Each independently represents H or methyl, and wherein X represents halogen, preferably Cl. In other or additional embodiments, the charged tail group is formed by a metal salt of a weak organic acid, such as Figure 3B As shown in , wherein M represents an alkali metal, preferably Na. In some embodiments, the second ligand can be formed in situ, for example as a product of a reaction in the second phase liquid 20. In situ generation of the second ligand (3), for example as a dissociation product of the corresponding disulfide, can expand the number of available ligands, for example to ligands that may lack commercial availability. Suitable reactions include forming acid adducts of weak organic bases and forming metal salts of weak organic acids by reaction of a strong acid or a strong base with a corresponding weak organic base or a weak organic acid, respectively. Suitable second ligand 3 moieties can also be dissociation products of corresponding disulfide precursor moieties.

[0074] Exemplary second ligands 3 as described herein include cysteamine hydrochloride ( Figure 3E )、2-sulfanylethanesulfonate sodium ( Figure 3D ) and 2-(dimethylamino)ethanethiol hydrochloride ( Figure 3F ).

[0075] The inventors have found that for the types of second ligands 3 as described herein (e.g., FIG. 3A to FIG. 3F As mentioned above, N,N-dimethylformamide, N-methylformamide or a combination thereof are particularly suitable as the polar solvent 21.

[0076] Inks comprising quantum dots capped with a layer of cysteamine hydrochloride, cysteamine hydrobromide, sodium 2-sulfanylethanesulfonate, potassium 2-sulfanylethanesulfonate, or 2-(dimethylamino)ethanethiol hydrochloride were found to be stable for at least 24 hours. Quantum dots capped with a layer of cysteamine hydrochloride, cysteamine hydrobromide, sodium 2-sulfanylethanesulfonate, potassium 2-sulfanylethanesulfonate, or 2-(dimethylamino)ethanethiol hydrochloride were found to be particularly suitable for making photoactive layers for optoelectronic devices such as solar cells, near-infrared photodetectors, and X-ray detectors.

[0077] The contact time can be determined by process conditions, including but not limited to the concentration of quantum dots in the first phase liquid and / or the concentration of the second ligand in the second phase liquid, process temperature and stirring conditions. In order to reduce the contact time, the method preferably includes stirring (e.g., shaking or stirring) the first phase liquid and the second phase liquid in contact to increase the contact area between the phases. Preferably, the contact between the first phase liquid and the second phase liquid stops after the reaction is completed, preferably within 1 hour or faster after the ligand exchange is completed. Stopping the reaction preferably also includes separating the quantum dots formed by the shell-terminated second ligand from the second phase liquid (polar solvent). Stopping the reaction faster reduces the possibility of contamination and / or quantum dot degradation, for example due to Oswald ripening. Typically, the contact time is on the order of seconds or minutes, up to several hours, for example about 30 seconds, about 1 minute to 5 minutes, about 15 minutes to 1 hour, or more. The progress of ligand exchange can be determined experimentally, for example, by chemical analysis and / or optical determination, to minimize the contact time.

[0078] The amount of the second ligand in the second phase (concentration times volume) is in excess relative to the number of available binding sites on the quantum dots. The amount of the second ligand in the second phase is at least sufficient to replace the aliphatic ligands of the quantum dots, preferably all aliphatic ligands. The required amount can be determined experimentally. The progress of the ligand exchange reaction can be followed, for example, visually. The inventors have found that the speed and completeness of the ligand exchange are related to the concentration of the second ligand. The inventors have found that the higher the concentration of the second ligand, the faster the exchange reaction can proceed. The concentration of the second ligand in the second phase is at least 100 micromolar (μM). Preferably higher, for example at least 1 millimolar (mM) or at least 10 mM or higher, for example about 30 mM. The maximum solubility of the second ligand in the second phase can determine the upper concentration limit. Typically the concentration is less than 90% of the maximum solubility

[0079] In a preferred embodiment, the amount of the second ligand dissolved in the polar solvent 21 is no more than about 1.5 times the predetermined required amount of the second ligand, preferably less than 1.05 times, relative to the amount required to completely cap the quantum dot 1 by the shell 3s of the second ligand. The exact amount of the second ligand to be added can be determined experimentally. Too low an amount may result in incomplete or partial transfer of the quantum dots from the first phase liquid to the second phase liquid, which can be visually observed. The presence of excess ligand can be determined, for example, by analyzing the solvent, such as the supernatant obtained after centrifugation. Alternatively, thermogravimetric analysis (TGA) can be used to measure the amount of the second ligand to be added. This amount can be related to the mass fraction of the first ligand bound to the colloidal nanoparticles. Typically, the ligand fraction in the colloidal PbS sample capped with oleic acid is 10 wt% to 50 wt% of the total weight (the weight of the QD core and the capping layer of the first ligand). Assuming that TGA analysis of a given QD composition shows a 30 wt% mass fraction of oleic acid, and considering the molar mass of the ligand (282.45 g / mol), it can be calculated that a 1 mL sample containing 20 mg / mL of this QD composition should be contacted with an amount of at least 21.2 micromolar of the second ligand.

[0080] In some embodiments, the concentration of QDs in the first phase liquid is about 0.5 mg / ml to 100 mg / ml, such as 50 mg / ml, 30 mg / ml, 20 mg / ml, 10 mg / ml, 5 mg / ml or 1 mg / ml. In order to enhance mixing, the relative volumes of the first phase liquid and the second phase liquid are preferably about 3:1 to about 1:3, and more preferably the volumes of the first phase liquid and the second phase liquid are approximately equal. Typically, for 1 ml of the first phase liquid containing about 20 mg / ml PbS QDs, about 1 ml of the second phase liquid containing about 30 mM of the second ligand is used. Preferably, the excess free ligand is small. Preferably, the amount of the second ligand 3 is about 1 to 1.01 times the predetermined required amount. By providing a second ligand close to the predetermined required amount, the quantum dots can be terminated by the shell of the second ligand while minimizing the amount (concentration) of the free (unbound) ligand in the polar solvent. In other words, the amount of added ligand moiety is preferably such that after the ligand exchange reaction, the resulting suspension of quantum dots terminated by the shell of the second ligand has a concentration of free, unbound ligand moieties in solution that is close to zero. By minimizing the amount of free ligand moieties in the ink, the interparticle spacing in the dense layer formed by such ink can be further reduced, for example, further mitigating the increase in interparticle spacing due to the presence of free ligands. Therefore, in some embodiments, the method includes a step of determining the required amount of the second ligand to be dissolved in the polar solvent 21 relative to the amount required to terminate the quantum dots 1 by the shell 3s of the second ligand.

[0081] In some embodiments, the step of determining the predetermined required amount can be performed in a separate experiment. The step of determining the predetermined required amount need not be included in each manufacturing cycle. The amount of the second ligand added to the polar solvent 21 can be calculated from data obtained from a separate earlier experiment (e.g., depending on the type and / or quality of the quantum dots).

[0082] Figure 4A Another step of making the ink composition is schematically depicted. In a preferred embodiment, for example, as shown in the figure, the method of making the ink composition includes dispersing the separated quantum dots 1 capped by the shell 3s of the second ligand in the polar printable liquid medium 30. The printable liquid medium 30 can be added from a separate container 52 to a container 53, the container 53 containing, for example, separated particles of quantum dots 1 capped by the shell 3s of the second ligand, or vice versa. The ink may contain one or more additives 31, 32. Additives include, but are not limited to, dopants, wetting agents, fillers, stabilizers and polymers. Figure 4B A container containing an ink composition 100 including a p-type dopant 31 and additional additives 32 is schematically depicted.

[0083] The inventors further discovered that the dried composition of quantum dots terminated by the shell of the second ligand can be dispersed (e.g., redispersed) in a polar solvent composition, such as a second polar solvent different from the first polar solvent during the ligand exchange process. The inventors discovered that the presence of charge in the shell helps disperse and stabilize quantum dots 1.

[0084] The polar solvent composition (second polar solvent) in the ink may or may not have the same composition as the solvent contained in the second phase liquid 20. Separating the quantum dots capped by the shell of the second ligand from the second phase comprising the first polar solvent and redispersing the quantum dots in a liquid of a different polarity (e.g., a liquid printing medium) allows the properties of the ink to be optimized independently of the selection criteria controlled by the ligand exchange process.

[0085] The step of dispersing the isolated quantum dots need not be performed directly after the separation step. The inventors have found that the isolated quantum dots terminated by the shell of the second ligand can be advantageously stored for a long time without substantial loss of functionality. The inventors have found that the isolated quantum dots can be stored for a period of more than four weeks before being used to formulate a printable ink. The isolated quantum dots terminated by the shell of the second ligand, such as pellets of precipitated or settled quantum dots 1, are preferably dried, for example under vacuum, preferably immediately after separation and before further use.

[0086] Printable ink compositions can be understood as any medium that allows for convenient and reliable deposition of films of quantum dots on a target substrate. Suitable deposition methods include, but are not limited to, inkjet printing, blade coating, doctor blade, spin coating, slot die coating, spraying, or any other known application method for depositing a liquid. After the film is dried, the substrate can be coated with a film or dense (dried) layer of quantum dots terminated by the shell of the second ligand. Thus, printable ink compositions can be used to manufacture various electronic devices, such as for the manufacture of dense layers, such as photoactive sensing layers, for sensing applications, such as near-infrared photodetectors or X-ray detectors. Such dense active layers can be manufactured by depositing and drying a layer of the ink composition (e.g., covering a set of electrodes) on a target substrate.

[0087] For inks intended for use in the manufacture of optoelectronic sensing layers of electronic devices such as X-ray detectors, quantum dots are preferably based on heavy metal compounds. Preferably, in such an embodiment, the quantum dots contain heavy atoms, such as PbS, PbSe. Typically, in large crystals, the band gaps of PbS and PbSe are very small and unsuitable for electronic applications. Advantageously, in the form of quantum dots, the band gap is increased, and films of PbS quantum dots can be used as photosensitive semiconductors with variable band gaps (0.8 eV to 1.4 eV, more or less). Quantum dots based on heavy metals are particularly suitable as components of photoactive layers in devices for X-ray detection.

[0088] In some embodiments, for example, Figure 4A and Figure 4B As shown in , the printable liquid medium contains a p-type dopant 31 or an n-type dopant (not shown). The dopant can be of organic and / or inorganic nature. Depending on the specific compound, various coordination compounds of transition metals can be used as n-type or p-type dopants. The p-type dopant can be any known type of dopant, including: organic p-type dopants, such as TCNQ (tetracyanoquinodimethane) and / or polymeric p-type dopants; and inorganic p-type dopants, such as nanoparticles such as NiO or WO 3 Nanoparticles and / or Fe 3+ Salts such as FeCl 3 or FeBr 3 The n-type dopant may be any known type of dopant, including: organic n-type dopants such as TBAF (tetra-n-butylammonium fluoride) and n-DMBI (4-(2,3-dihydro-1,3-dimethyl-1H-benzimidazol-2-yl)-N,N-dimethylaniline) and / or polymeric n-type dopants; and inorganic n-type dopants such as nanoparticles such as ZnO or SnO 2 Nanoparticles or alkali metal compounds such as Cs 2 CO 3 or Rb 2 CO 3Preferably, the dopant should be miscible with the second polar solvent at a sufficient concentration. The optimum dopant concentration depends on the type of quantum dot and the intended application, and can be found experimentally for a given combination of dopant and quantum dot film.

[0089] The printable liquid medium comprises a polar solvent (second polar solvent) or a mixture of polar solvents 30 to disperse the quantum dots 1 capped by the shell 3s of the second ligand 3. In some embodiments, the second polar solvent consists essentially of pure water, i.e., water without a co-solvent. The pH of the printable liquid medium is preferably such that the tail group remains substantially charged, so that the capping layer does not lose its stabilizing properties due to protonation or deprotonation of the charged tail group of the second ligand. For water-based inks in which the second ligand comprises a conjugate base of an acid, the concentration of protons in the ink is preferably at least an order of magnitude lower than the equilibrium pH of a pure solution of the corresponding weak acid (pH≤pKa-1). For water-based inks in which the second ligand comprises a conjugate acid of a base, the concentration of protons in the ink is preferably at least an order of magnitude higher than the equilibrium pH of a pure solution of the corresponding base (pH>pKa+1). Other pH limits of the ink (i.e., maximum pH or minimum pH, respectively) can be controlled by the known or individually determined stability of the quantum dots, such as stability to etching. For quantum dots capped with cysteamine hydrochloride, satisfactory ink colloidal stability was observed for printable liquid media with a pH of about 1 to about 9. For quantum dots capped with sodium 2-sulfanylethane sulfonate or potassium 2-sulfanylethane sulfonate, satisfactory ink colloidal stability was observed for printable liquid media with a pH of about 7 to about 13.

[0090] The concentration of quantum dots terminated by the shell of the second ligand can vary over a wide range. The preferred quantum dot concentration depends on the application and the film deposition method. The quantum dot concentration in the ink can be a wide range of about 0.1 or 1 mg / ml to about 300 mg / ml. High concentrations can advantageously allow thick dry films to be deposited in a single deposition operation. Too high a concentration can impair the long-term stability of the ink. It was found that inks with a quantum dot concentration of about 1 mg / ml to about 100 mg / ml, preferably about 3 mg / ml to about 50 mg / ml, produced a good balance between ink stability and the quality of the deposited film.

[0091] like Figure 4B As shown, the printable liquid medium may contain one or more other additives as disclosed herein. The type and amount of additives depends on the intended application.

[0092] In some embodiments, the ink comprises a stabilizer. Stabilizers (e.g., antioxidants) can stabilize degradable (e.g., oxidized) ligands. For example, if the ligand comprises a thiol or disulfide group that can be easily oxidized (e.g., by oxygen), the stabilizer can be added to the liquid medium. Examples of such stabilizers include, but are not limited to, dithiothreitol, glutathione, β-mercaptoethanol, sodium borohydride, tris(2-carboxyethyl)phosphine, ascorbic acid, N-acetylcysteine, γ-glutamylcysteine, and bacillus mercaptan (bacillithiol).

[0093] In some embodiments, the ink includes a wetting agent. After the ink layer is deposited on the target surface, and after the lower boiling point solvent evaporates, the wetting agent is believed to remain in the dense film of quantum dots, in which case it is found that the wetting agent improves the properties of the formed film, such as morphology. The improvement of film properties can be observed experimentally, for example, by the improved optoelectronic properties of the film, for example, in a sensing layer for an X-ray detector. In some embodiments, the wetting agent is pyrrolidone. Compared with an ink that does not contain pyrrolidone, pyrrolidone (e.g., 2-pyrrolidone) can further improve the wettability of the ink and / or reduce the surface tension of the ink, thereby enabling the deposition of a more uniform quantum dot film. By monitoring the morphology and / or electrical response of the deposited film, the concentration of pyrrolidone in the ink can be experimentally found. Similar to the presence of excess ligands, excess pyrrolidone can increase the spacing between adjacent quantum dots in the deposited dense film. Therefore, in practice, in particular for inks for the deposition of dense quantum dot layers for optoelectronic applications (such as X-ray detectors), the amount (mass) of pyrrolidone added is less than 10% of the mass of the second ligand contained in the ink, preferably less, such as less than 5%, for example 0.1 to 1 weight percent.

[0094] In other or additional embodiments, the ink comprises one or more polymer additives 33 . Figure 3GExemplary polymer additives 33a, 33b, 33c for inks as described herein are schematically depicted. It was found that polymer additives improve the printing properties of the ink. It was found that polymer (non-conjugated polymer) additives, preferably branched polymer additives, improved ink properties such as sprayability (droplet stability), thereby promoting the deposition of a uniform ink layer. Suitable polymers include, but are not limited to, branched polyethylene imine 33a, poly (acrylic acid) 33b and poly (sodium 4-styrene sulfonate) 33c. It was also found that the incorporation of charged polymer additives can improve the quality of the deposited layer. The inventors found that the observed improvement is related to improved adhesion of the layer to the substrate, thereby reducing delamination. Alternatively or additionally, the polymer can act as a matrix for quantum dots, such as in a film formed after drying the ink layer. Dielectric polymers or other dielectric molecules can reduce dark current in a photoelectrically active sensing layer of an imaging device. Examples of suitable dielectric polymers include, but are not limited to, polyethylene glycol, poly (methyl methacrylate), polyethylene imine, polyvinyl pyrrolidone and polyvinyl alcohol. Conductive polymers may be incorporated to improve the printing properties of the ink while maintaining the conductive properties of the additive. Suitable conductive materials include conductive polymers, including but not limited to polythiophene, PFNI-B (poly[(9,9-bis(3,3'-N,N'-trimethyl-ammonium)propylfluorenyl-2,7-diyl)-alternative-co-(1,4-phenylene)] diiodide salt) and water-soluble fullerene derivatives such as WSC70PI (Solaris Chem Inc.).

[0095] The concentration of the polymer additive can be determined experimentally. For a branched PEI with a Mw of about 25 kDa, the appropriate additive concentration for an ink with a quantum dot concentration of 20 mg / ml was experimentally determined to be 0.5 mg / ml to 2.5 mg / ml. For inks of other concentrations, the additive level can be adjusted accordingly.

[0096] In some preferred embodiments, the polar solvent in the printable liquid medium consists of a mixture of water and ethylene glycol, wherein the volume fraction of ethylene glycol in the mixture is 5% to 50%. It was found that inks whose liquid medium is essentially formed by water show poor wetting behavior, such as the rupture of the deposited liquid film, which is considered to be the result of the high surface tension of water. It was found that the addition of ethylene glycol improves the wetting behavior and / or improves film formation. From a cost and / or environmental perspective, a high proportion of water is preferred. The inventors have found that due to the high boiling point, part of the ethylene glycol can initially remain bound to the film when deposited. The inventors have found that after complete drying, the evaporation of this residue can lead to significant undesirable volume shrinkage of the film. Therefore, the volume fraction of ethylene glycol in the mixture is preferably 10% to 30%.

[0097] In other preferred embodiments, the polar solvent printable liquid medium 30 is at least partially fluorinated lower alcohol. It can be understood that lower alcohol includes alcohols with a total number of carbon atoms n of 6 or less. Compared with water and / or a mixture of water and ethylene glycol, at least partially fluorinated lower alcohols or mixtures thereof advantageously have relatively low surface tension. It is found that when deposited on a substrate, inks with relatively low surface tension show improved wetting behavior. Compared with water and / or ethylene glycol, at least partially fluorinated lower alcohols advantageously have high vapor pressures compared with water. It is found that when deposited on a substrate, inks containing solvents with relatively high vapor pressures advantageously show improved, such as faster and / or more complete drying. It is found that quantum dots terminated by dimethyl (amino) ethanethiol show excellent colloidal stability in at least partially fluorinated lower alcohols such as 2,2,2-trifluoroethanol and hexafluoroisopropanol. In addition, ternary solvent blends including fluorinated alcohols, water and ethylene glycol may be advantageous. Fluorinated alcohol (FA) can effectively reduce surface tension, thus can reduce the fraction of ethylene glycol. Therefore, less ethylene glycol will be retained in the film. In some preferred embodiments, the blend comprises 20 vol% to 50 vol% FA, 40 vol% to 80 vol% water and 3% to 10% ethylene glycol.

[0098] As about Figure 2B As shown and described, aspects of the invention relate to dried compositions comprising quantum dots terminated by the shell of a second ligand 3 obtainable by any of the methods described herein, wherein the method further comprises drying the isolated quantum dots terminated by the shell of a second ligand. In some embodiments, the composition is substantially formed by quantum dots terminated by the shell of a second ligand 3. In other embodiments, the dried composition may include one or more additives, such as stabilizers, dopants, etc. described herein. These dried compositions may be stored prior to use in formulating ink compositions.

[0099] As shown and described with respect to Figures 1 to 4 and according to the method aspects of the present invention, the present invention relates to an ink composition comprising quantum dots capped by a shell of polar organic ligands. The ink composition comprises

[0100] -A quantum dot suspension in a polar printable liquid medium 30, wherein the quantum dots are capped by a shell 3s of a second ligand 3, wherein the second ligand 3 has a molecular structure comprising: at least one surface-binding head group 3h having an affinity for binding to a surface site of the quantum dot; and an ionically charged tail group 3t and a counter ion 3c associated therewith.

[0101] In a preferred embodiment, the amount of free unbound ligand fraction in the ink is below 10 μM, preferably lower, such as <1 μM. Most preferably, the ink composition is substantially free of unbound (free) ligand fraction.

[0102] In some embodiments, the solvent contained in the ink consists of a mixture of water and ethylene glycol, wherein the volume fraction of ethylene glycol in the mixture is 10% to 50%.

[0103] In other embodiments, the solvent contained in the ink consists of an at least partially fluorinated lower alcohol.

[0104] In other or additional embodiments, the liquid printable liquid medium further comprises a p-type dopant or an n-type dopant.

[0105] As described herein, the ink 100 and its manufacturing method as described herein are particularly suitable for manufacturing dense layers comprising quantum dots terminated by shells 3s of second ligands 3. These dense layers are suitable as sensing layers for many optoelectronic applications, including solar cells, photodetectors and X-ray sensors or even imaging devices with improved optoelectronic properties. The present invention provides a solution for large-scale manufacturing of high-quality thick (>1 micron) semiconductor PbS QD films under ambient conditions, which can detect X-ray radiation with 10-fold sensitivity compared to a-Se detectors. Therefore, the present invention relates to the use of inks, such as in manufacturing methods for manufacturing imaging devices. The inks can also be advantageously used in other electronic devices such as field effect transistors (FETs), solar cells, light emitting FETs (LEFETs), photodetectors and phototransistors for visible light, IR or gamma radiation.

[0106] Figure 5 Schematically shown is a cross-sectional view of an imaging device 1000 including a photoactive layer 110 fabricated using an ink 100 as described herein. Fabrication of the imaging device 1000 includes at least:

[0107] - depositing one or more layers of an ink composition comprising a p-type dopant as described herein or an ink obtainable by a method as described herein, for example on a substrate comprising an electrode structure; and

[0108] - depositing one or more layers of an ink composition comprising an n-type dopant as described herein or an ink obtainable by a method as described herein; and

[0109] A stack of photoactive layers 110 including at least p-type photoactive layer 110p and n-type photoactive layer 110n is formed, wherein the photoactive layers are amorphous including a disordered structure of quantum dots deposited by applying a corresponding ink composition.

[0110] In one embodiment, if Figure 5 As shown, the imaging device 1000 includes a stack of photoactive layers 110 including at least a p-type photoactive layer 110p and an n-type photoactive layer 110n. The term n-type refers to the electron “e- ", and means that electrons are the majority carriers in the semiconductor layer, while holes are the minority carriers. In contrast, the term p-type refers to the hole "h + ", and means that holes are the majority carriers in the semiconductor layer, while electrons are the minority carriers. Figure 5 As shown, light having a wavelength λ can generate exciton electron-hole pairs, where the charges can be separated to flow to different electrodes 130t, 130b.

[0111] Typically, n-type or p-type semiconductors are produced by doping intrinsic semiconductors with donor impurities. Alternatively or additionally, the type of layer can be determined by appropriate selection of ligands. In a preferred embodiment, one or more, preferably all, photoactive layers comprise quantum dots (QDs) formed from ligand-terminated semiconductor quantum dots as described herein.

[0112] The photoactive layer is amorphous, for example comprising a disordered structure of quantum dots. Advantageously, the ink as described herein advantageously produces an amorphous photoactive layer comprising a disordered structure of quantum dots deposited by applying a corresponding solution comprising colloidal quantum dots (CQDs). The formation of an amorphous photoactive layer comprising a disordered structure of quantum dots is believed to be related to the presence of a charged capping layer surrounding the quantum dots. Preferably, each type of photoactive layer is deposited in a single (fluid) processing step, for example by spraying, rather than layer by layer. Advantageously, the ink as described herein advantageously can have a concentration of 1 mg / mL to 300 mg / mL of quantum dots 1 capped by the shell 3s of the second ligand 3, which is within the range of photoactivity and allows deposition, for example by spraying the photoactive layer in a single fluid processing step. By setting the quantum dot concentration, a layer with a thickness on the order of micrometers can be obtained, for example, a layer of 100 to 500 nanometers or a layer with a thickness of 1 to 1000 micrometers.

[0113] In some embodiments, the quantum dots are substantially separated by ligands, e.g., there is no inorganic matrix between them. In some embodiments, the type of photoactive layer is at least partially determined by the inorganic dopant added to the layer. In other or additional embodiments, the type of photoactive layer is determined only, substantially, or primarily by the inorganic dopant added to the layer. In one embodiment, the layers differ only in the type of inorganic dopant. Alternatively or additionally, it is contemplated to use organic molecules / polymers as the matrix.

[0114] The imaging device 1000 includes a readout electronic device including electrodes 13t, 13b (with other layers therebetween) sandwiching a photoactive layer 110. Typically, at least one of the electrodes 13b is divided into a respective pixel 100p for collecting photogenerated charge from a respective portion of the photoactive layer. In a preferred embodiment, each pixel 100p includes an amplification circuit to amplify the photogenerated charge, which will be described in further detail below.

[0115] In a preferred embodiment, as shown, the stack of photoactive layers 110 includes at least three different types of photoactive layers, including an intermediate photoactive layer 110i between a p-type photoactive layer 110p and an n-type photoactive layer 110n.

[0116] Suitable materials for semiconductor quantum dots 1 may depend on the application. For example, PbS and PbSe quantum dots are well suited for absorption of visible and near to mid-infrared light, CdSe is suitable for visible light, and PbS, PbSe, CdTe are suitable for absorption of X-rays and gamma rays.

[0117] Optionally, as shown, additional layers can be added to the stack. In the embodiment shown, the electron transport layer 120e is disposed between one of the electrodes 130t and the n-type photoactive layer 110n. In the embodiment shown, the hole transport layer 120h is disposed between the other electrode 130b and the p-type photoactive layer 110n. Typically, the top electrode 130t is transparent to at least the wavelength λ measured by the detector. Alternatively, the stack can be inverted, for example using a transparent substrate and bottom electrode (not shown).

[0118] In some embodiments, for example, Figure 1A As shown, the scintillating layer 210 is disposed between the stack of photoactive layers 110 and the front side of the device 1000 for receiving light. For example, the scintillating layer can be configured to convert lower wavelength (high frequency) radiation such as X-rays into higher wavelength (low frequency) light such as visible light or near infrared. In addition, the quantum dots can be configured, for example, to have a certain size and material to absorb visible light or near infrared light converted by the scintillating layer, thereby allowing detection of lower wavelengths. In this way, an X-ray detector can be provided. Of course, the scintillating layer shown can also be omitted in other embodiments to provide, for example, a visible light sensor. For example, in these or other embodiments, the intermediate photoactive layer 110i can include relatively small quantum dots. For example, the quantum dots include lead sulfide (PbS) or other materials.

[0119] As described herein, relatively small quantum dots may have an average or median diameter of less than 4 nanometers. This may allow, for example, visible light absorption. In contrast, relatively large quantum dots may have an average or median diameter of greater than 4.5 nanometers. This may allow, for example, infrared light absorption.

[0120] In some embodiments, the intermediate photoactive layer 110i comprises relatively large quantum dots compared to the quantum dots in the p-type photoactive layer 110p and the n-type photoactive layer 110n. For example, the relatively large quantum dots in the intermediate photoactive layer 110i may be at least 1.1 times, 1.2 times, 1.5 times or more larger. For example, the quantum dots in the intermediate photoactive layer 110i may be >4.5nm. This may provide a relatively small band gap to absorb (near) infrared light. So in this way, a near infrared detector may be provided.

[0121] In some embodiments, for example, Figure 1A As shown, the layer thickness Di of the intermediate photoactive layer 110i is, for example, at least two, five, ten, one hundred or even one thousand times greater than the layer thickness Dp, Dn of the p-type photoactive layer 110p and the n-type photoactive layer 110n. For example, the typical layer thickness Dp and / or Dn of the n-type photoactive layer 110p, 110n is preferably 10 nm to 100 nm, more preferably 20 nm to 50 nm. For example, according to Figure 1A In embodiments of the visible light or x-ray sensor or according to the (near) infrared sensor, a typical layer thickness Di of the intermediate photoactive layer 110i is preferably from 100 nm to 1000 nm, more preferably from 100 nm to 500 nm, more preferably from 200 nm to 300 nm.

[0122] In some embodiments, the thickness of the intermediate layer can be on the order of microns, such as 1 micron to 1000 microns, preferably 10 microns to 100 microns. For example, quantum dots in a relatively thick intermediate layer can provide a direct conversion radiation sensor in which the quantum dots absorb ionizing radiation. Preferably, in such embodiments, the quantum dots include relatively heavy atoms and have a large band gap, such as PbS or other materials with a diameter less than 4 nanometers.

[0123] Example

[0124] Aspects of the invention will now be illustrated by the following non-limiting examples.

[0125] In a first embodiment, a dispersion of oleate-capped PbS quantum dots in 1 ml of hexane with 20 mg / ml quantum dots is transferred to a vial containing 1 ml of 30 mM cysteamine hydrochloride in DMF (or 30 mM MESNA in NMF). The vial is shaken at room temperature until all the QDs are transferred to the polar phase. This takes about 30 s. The progress of the reaction is followed by monitoring the color of each phase. At the beginning of the ligand exchange process, the colored quantum dots are contained in the non-polar phase. The transfer of color to the polar phase is an indication of the formation of a colloidal suspension of quantum dots 1 capped by the shell of the second ligand in the polar phase. Fig. 6A The observed color changes are schematically depicted. Shown on the left is a vial 50 containing a first phase liquid 10 and a second phase liquid 20 at the beginning of the ligand exchange process LE (compare Figure 1A ). The vial 50 containing the first phase liquid 10 and the second phase liquid 20 after the ligand exchange process LE is completed is shown on the right (compare Figure 2A ). The experiment was repeated using NMF as solvent with similar results. When DMSO or water was used as solvent in the second phase liquid 20, incomplete ligand transfer was observed.

[0126] After ligand exchange is complete, the non-polar phase is discarded and the polar phase is washed three times with 1 ml of hexane. The QDs are then precipitated by centrifugation. After centrifugation, the supernatant is discarded and the pellet is dried under vacuum until the remaining solvent evaporates. Alternatively, the pellet can be kept in a nitrogen environment until the device is fabricated. The pellet is dispersed in a 80 / 20 volume / volume water / ethylene glycol mixture shortly before device fabrication.

[0127] Fig. 7A Depicted is a scanning camera image of the emission from PbS QDs capped with cysteamine hydrochloride in water. The arrow follows the trajectory of increasing units according to the color scale.

[0128] Figure 7B Depicted is the photoluminescence spectrum of PbS QDs capped by cysteamine hydrochloride in water.

[0129] Fig. 8A Time-resolved photoluminescence (TRPL) spectra of PbS QDs capped by cysteamine hydrochloride in water are depicted. The PL lifetime was determined to be 1.1 μs.

[0130] It was found that the ligand exchange process according to the present invention can be scaled up to multi-gram scale without substantially affecting the properties of the formed QDs. Figure 8C The photograph of the 1 L separatory funnel containing the two-phase mixture after complete ligand exchange is shown to illustrate the potential for scaling up of this approach.

[0131] Figure 8BDepicted are the absorption spectra of PbS QDs capped with native oleic acid in hexane (solid black line) and after ligand exchange with cysteamine hydrochloride in water (dashed grey line).

[0132] In a second example, the procedure of Example 1 was successfully repeated for CdSe quantum dots capped with oleic acid. Figure 6C A photograph of a vial 50 containing a second phase liquid 20 and quantum dots 1 capped with a shell of a second ligand at the bottom of the vial after centrifugation is shown.

[0133] In a third example, the steps of Example 1 were repeated for Au quantum dots 1 capped with oleylamine in heptane. Figure 6B A photograph of a vial 50 containing an ink 100 comprising quantum dots 1 capped with a shell of a second ligand redispersed in water is shown. Fig.6D A photograph of a vial 50 containing ink 100 comprising the CdSe quantum dots of the third embodiment redispersed in water is shown.

[0134] In the fourth, fifth and sixth examples, the experiments of Examples 1 to 3 were repeated using sodium 2-sulfanylethanesulfonate as the second ligand. In these examples, 1 mL of acetone (anti-solvent) was added to the second phase to precipitate the quantum dots. For systems using cysteamine hydrochloride DMF, adding an anti-solvent is feasible, but not necessary. The other results were comparable.

[0135] In the seventh embodiment, the ligand exchange process was repeated for PbS quantum dots terminated with oleic acid using the disulfide of cysteamine hydrochloride as the second ligand. The disulfide of cysteamine hydrochloride was found to be poorly soluble in DMF but soluble in DMSO. Therefore, other similar methods were performed using DMSO as solvent. Complete ligand exchange was observed, and pellets of PbS quantum dots terminated with shells of cysteamine hydrochloride ligands were obtained after centrifugation.

[0136] QDs and ink compositions as described herein can be particularly beneficial in optoelectronic devices. With reference to Figures 9 to 14, various aspects and benefits of QDs according to the present invention, and their applications in optoelectronic devices, such as field effect transistors, photodetectors such as infrared photodetectors and X-ray detectors, photodiodes, and solar cells, will be explained. Unless otherwise stated, the devices are prepared using generally known procedures.

[0137] Fig. 9A Output characteristics of an exemplary field effect transistor fabricated with cysteamine hydrochloride-capped PbS QDs as the active material are shown. Note that the figure shows both reverse and forward scans, indicating very low hysteresis.

[0138] Fig. 9BPlotting the transfer characteristics of a field effect transistor. The solid line represents the forward scan and the dashed line represents the reverse voltage scan. The linear mobility of electrons is found to be 3.1E-4cm 2 / Vs.

[0139] Fig. 10A Schematically depicted is a device schematic of an infrared photodetector made from a photoactive layer comprising cysteamine HCl-terminated PbS QDs according to the present invention. The QDs were sprayed in air on top of a glass / ITO substrate coated with 100nm ZnO nanoparticles to form a 600nm thick layer. The device was completed by thermal evaporation of 7nm MoOx and 80nm gold top contacts.

[0140] Fig. 10B The optical properties of cysteamine HCl-capped quantum dots deposited as a thin film (600 nm) as a photoactive layer in an infrared photodetector are shown. It shows a clear absorption peak in the infrared region (at 1450 nm), which is slightly red-shifted compared to the original OA-capped quantum dot solution (at 1420 nm). Light scattering in the quantum dot film leads to an increase in the measured absorption value and explains the non-zero absorption at wavelengths longer than the absorption peak position.

[0141] Fig.11A The JV curve of the photodiode in the dark is plotted. The device has 3.4*10E-4mA / cm for 1V reverse bias. 2 The cut-off current is Fig. 10B The absorption characteristics of the quantum dots shown are low values. The diode exhibits a current rectification ratio of 6.2*10E3, which indicates good charge transport in the forward direction and effective charge carrier blocking in the reverse direction.

[0142] For external quantum efficiency (EQE) measurements, the current response was measured under short-circuit conditions (photocurrent mode of operation, V = 0 V) ​​while illuminating an area of ​​the device (4x4 mm 2 ). Fig. 11B The corresponding responsivity curves are depicted.

[0143] Based on the responsivity curve, the EQE value is calculated ( Fig. 12A ). The measured EQE (bottom, black curve) reaches 9.5% at 1450nm. Because the ITO electrode causes a considerable loss in EQE, a correction was implemented (top, red curve). This shows that the internal quantum efficiency (IQE) reaches 15.4% with an absorption of 55% (uncorrected for the scattered and unabsorbed portion of light). Therefore, 15.4 / 55=28% of the absorbed or scattered infrared photons are converted into charge and extracted from the device without applying a reverse bias.

[0144] To calculate the specific detectivity D*, the device was measured in the dark and under monochromatic illumination at reverse bias. Fig. 12B The dark current of the display device and the current measured under 1450nm monochromatic light (860nW) at reverse bias of 0.1V, 0.5V and 1V. When the dark current is dominated by shot noise, D* can be expressed as follows:

[0145]

[0146] where R is the responsivity and J dark is the dark current density.

[0147] This gives values ​​for the specific detectivity of 1.3E12 Jones for 0.1 V, 9.6E11 Jones for 0.5 V, and 7.2E11 Jones for 1 V bias.

[0148] Fig.13A The JV characteristics of a solar cell according to the present invention under AM 1.5 light illumination are shown, the solar cell comprising an active layer of PbS QDs capped by cysteamine HCl. The device was found to have a short circuit current J of 18.6 mA / cm^2 SC ; 0.5V open circuit potential V oc ; Fill factor FF is 0.48; and maximum power point (MPP) is 4.46mW / cm 2 .

[0149] Fig. 13B The X-ray sensitive photodiode (e.g. Figure 5 The thickness of the QD layer is 600 nm.

[0150] Fig.14A The current response of the device to X-ray pulses (~10 s each) (HP Haxitron 43855A, tungsten anode, 58 kV voltage, 2 mA current) is depicted for a reverse voltage of 1 V. The rise time is limited by the source on time, and the fall time is limited by the measurement equipment. Fig. 14B The properties in terms of leakage current and X-ray response current are shown.

[0151] As a comparative example, the inventors attempted to prepare cysteamine hydrochloride-capped quantum dots according to the method disclosed by Hak Soo Choi et al. (Nature Biotechnology 25; 1165-1170 (2007)). For this purpose, an equal volume of chloroform solution of oleate-capped PbS QDs was mixed with 30 mL of cysteamine hydrochloride solution dissolved in aqueous PBS buffer. However, even after long-term stirring (>12 h), no ligand exchange (LE) was observed. In contrast, the ligand exchange process according to the present invention was completed after about 30 seconds.

[0152] In addition, ligand exchange was attempted in a hexane / water mixture (oleate-capped PbS QDs in hexane; cysteamine hydrochloride in water). The inventors unexpectedly discovered that ligand exchange can be facilitated by adding a third solvent to the two-phase mixture. The third solvent is miscible with hexane and water.

[0153] For the purpose of clarity and brief description, features are described herein as part of the same or separate embodiments, however, it should be understood that the scope of the invention may include embodiments having all or some combinations of the described features. For example, although embodiments are shown for certain quantum dots and ligands, those skilled in the art who benefit from the present disclosure may also conceive of alternatives to achieve similar functions and results. The various elements of the embodiments discussed and shown provide certain advantages, such as a general method for exchanging the non-polar ligand shell (e.g., natural ligand shell) of quantum dots for a tailored ligand shell that can be selected according to desired properties (e.g., solubility, colloidal stability, and / or optoelectronic properties). Of course, it should be understood that any of the above-mentioned embodiments or processes can be combined with one or more other embodiments or processes to provide further improvements in finding and matching designs and advantages. It should be understood that the present disclosure provides special advantages for the manufacture of inks for optoelectronic devices and is generally applicable to any application that benefits from quantum dots terminated with a specific shell of a second ligand.

[0154] In interpreting the appended claims, it should be understood that the word "comprising" does not exclude the presence of other elements or actions than those listed in a given claim; the word "a" or "an" preceding an element does not exclude the presence of a plurality of such elements; any figure marks in the claims do not limit the scope; several "means" may be represented by the same or different items or implementing structures or functions; unless otherwise specifically stated, any disclosed means or parts thereof may be combined together or divided into further parts.

Claims

1. A method for producing an ink composition (100) for depositing a photoactive layer of an optoelectronic device, the method comprising - providing a first phase liquid (10), the first phase liquid (10) comprising a non-polar solvent (11) and nanoparticles (1) dispersed in the non-polar solvent, the nanoparticles being terminated by a shell (2s) of a first ligand (2), the first ligand (2) comprising a surface-binding head group (2h) and an alkyl or alkenyl tail (2t), for at least initially maintaining the nanoparticles (1) in a colloidal suspension in the non-polar solvent (11); - providing a second phase liquid (20), wherein the second phase liquid (20) comprises a first polar solvent (21) and a second ligand (3) dissolved therein, wherein the second ligand has a molecular structure comprising: o a thiol head group (3h) for binding to a surface site of the nanoparticle (1); o an ionically charged tail group (3t) having a counterion (3c) associated therewith; and o an alkyl spacer having a total carbon number of 1 to 3 separating the head group and the tail group, a two-phase ligand exchange process, wherein the second ligand displaces the first ligand bound to the nanoparticle (1), thereby releasing the first ligand to the first phase liquid (10), the two-phase ligand exchange process comprising contacting the first phase liquid and the second phase liquid to form a dispersion of the nanoparticle (1) terminated by the shell (3s) of the second ligand (3) in the second phase liquid; Wherein the second ligand (3) is: in "n" is 1 to 3; "R1" and "R2" are each independently selected from H and methyl; "X" is halogen; and "M" is an alkali metal.

2. The method according to claim 1, comprising: - separating the nanoparticles terminated by the shell of the second ligand from the first polar solvent; and - Redispersing the separated nanoparticles (1) in a printable liquid medium (30) comprising a second polar solvent.

3. The method according to claim 2, wherein - the first polar solvent comprises N,N-dimethylformamide, N-methylformamide or a combination thereof; and - The second polar solvent comprises an at least partially fluorinated lower alcohol, or comprises a mixture of water and ethylene glycol, wherein the volume fraction of ethylene glycol in the mixture is 5% to 50%.

4. The method according to claim 1, comprising dissolving a disulfide moiety into the second phase liquid (20) to form the second ligand as a dissociation product of the disulfide moiety.

5. The method according to claim 1, comprising: - determining the amount of the second ligand to be contained in the first polar solvent (21) relative to the amount required to completely cap the nanoparticle (1) with the shell (3s) of the second ligand; and - providing the second phase liquid (20) comprising the first polar solvent (21) and a second ligand (3), wherein the amount of the second ligand (3) is less than 1.05 times the determined amount.

6. The method of claim 2, comprising washing the isolated nanoparticles with one or more portions of a solvent for the first ligand.

7. The method according to claim 1, comprising adding a third solvent to the first phase liquid (10) and the second phase liquid (20), the third solvent being miscible with both the non-polar solvent (11) and the first polar solvent (21).

8. The method of claim 1, wherein X is Cl and / or wherein M is Na or K.

9. An ink composition for depositing a photoactive layer of an optoelectronic device, the ink composition comprising - a colloidal suspension of nanoparticles in a printable liquid medium (30) comprising a polar solvent, wherein the nanoparticles are terminated by a shell of a second ligand (3) replacing an initial shell of a different first ligand, wherein the second ligand has a molecular structure comprising: o a thiol head group (3h) bound to a surface site of the nanoparticle (1); o an ionically charged tail group (3t) having a counterion (3c) associated therewith; and o an alkyl spacer having a total number of carbon atoms n of 1 to 3 separating the head group and the tail group, wherein the polar solvent comprises a lower alcohol that is at least partially fluorinated, or comprises a mixture of water and ethylene glycol, wherein the volume fraction of ethylene glycol in the mixture is 5% to 50%, Wherein the second ligand (3) is: in "n" is 1 to 3; "R1" and "R2" are each independently selected from H and methyl; "X" is a halogen; "M" is an alkali metal.

10. The ink composition of claim 9, wherein the composition is substantially free of the first ligand and free unbound second ligand.

11. The ink composition according to claim 9, wherein X is Cl and / or wherein M is Na or K.

12. The ink composition according to claim 9 or 10, comprising a pyrrolidone additive.

13. The ink composition according to claim 9 or 10, comprising one or more polymer additives (33).

14. The ink composition according to claim 9 or 10, comprising a p-type dopant (31) or an n-type dopant.

15. A method for manufacturing an imaging device (1000) comprising a stack of photoactive layers (110), the stack of photoactive layers (110) comprising at least a p-type photoactive layer (110p) and an n-type photoactive layer (110n), the method comprising: - depositing one or more layers of the ink composition comprising a p-type dopant according to claim 14; and — depositing one or more layers of the ink composition comprising an n-type dopant according to claim 14; The deposited layers form a stack of photoactive layers (110) comprising at least a p-type photoactive layer (110p) and an n-type photoactive layer (110n), wherein the photoactive layers are amorphous and comprise a disordered structure of nanoparticles formed of quantum dots deposited by applying a corresponding ink composition comprising colloidal quantum dots.

16. A dried composition comprising nanoparticles terminated with a shell of a second ligand (3) obtainable by: - Carry out the method according to claim 1; - separating the nanoparticles terminated by the shell of the second ligand from the first polar solvent of the second phase liquid; and - Drying the isolated nanoparticles.

17. Use of the dried composition according to claim 16 in the manufacture of a printable ink composition (100) by dispersing the dried composition in a polar solvent, the polar solvent comprising an at least partially fluorinated lower alcohol, or comprising a mixture of water and ethylene glycol, wherein the volume fraction of ethylene glycol in the mixture is 5% to 50%.

Citation Information

Patent Citations

  • Methods of making quantum dot films

    US20070174939A1

  • Water-soluble fluorescent nanocrystals

    US6251303B1

  • Conductive ink composition for inkjet printing

    CN101089058A

  • Fast, efficient and universal method for exchanging surface ligand of colloidal nanocrystal

    CN110386886A

  • Ligand-exchangeable nanoparticles and methods of making the same

    US20170362255A1